Risk of canine cranial cruciate ligament rupture is not associated with the major histocompatibility complex - Clements, D. N.; Kennedy, L. J.; Short, A. D.; Barnes, A.; Ferguson, J.; Ollier, W. E. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objectives: To investigate the association of the major histocompatability (MHC) class II allele haplotype frequencies with the diagnosis of cranial cruciate ligament (CCL) rupture in two breeds of dog.Methods: DNA samples from populations of Labrador Retrievers and Golden Retrievers with CCL rupture and general populations of the same breeds were characterised for three DLA class II loci (DRB1*, DQA1* and DQB1*) alleles using sequence-based typing or reference strand-mediated conformation analysis.Results: Although distinct differences in haplotype types, frequencies and homozygozity were observed between the two breeds, no disease specific association could be identified for the development of the CCL rupture within either population.Clinical significance: The risk for developing CCL rupture was not associated with DLA haplotype group(s) in Labrador Retrievers or Golden Retrievers, thus the hypothesis that there is an autoimmune basis to CCL rupture was not supported.
Keywords: MHC Class II; cranial cruciate ligament rupture; genetics; autoimmunity